Effects of short and long-term exposure to benzene, toluene, ethylbenzene, and xylenes (BTEX) in indoor environment air on human health: A systematic review and meta-analysis - Sedighe Afrasiabi; Marzieh Fattahi Darghlou; Younes Mohammadi; Mostafa Leili (Journal of Air Pollution and Health)
Today, because of the increasing level of people's need to improve wellbeing in social and individual life, air pollutants have been released that have Pollution harms both human health and the environment. This research examined Benzene, Toluene, Ethylbenzene, and Xylenes (BTEX) levels in indoor air across different global locations from 1963 to 2023. The investigation employed both; a systematic review and meta-analysis method. The health risks associated with long and short-terms exposure to benzene, toluene, ethylbenzene, and xylene were assessed. That average concentration benzene was 23.07 μg⁄m3, toluene was 131.60, ethylbenzene was 28.91, and xylene was 63.87. Also, the health risk assessment based on a 95% confidence level showed that the pollutants in question play a role in causing diseases such as lung neoplasm, stomach neoplasm, colon neoplasm, liver neoplasm, headache, dizziness, nausea, insomnia, etc. Consequently, it is crucial to implement stringent measures aimed at lowering the levels of these contaminants in indoor spaces.